Food security and livelihoods under a changing climate in Mozambique: preparing for the future - World Food Programme (World Food Programme, 2021)
Mozambique’s climate is characterized by relatively uniform temperatures across the country and a north-south rainfall gradient which results in higher more reliable rainfall amounts in the North, and lower more variable rainfall amounts in the South Historical climate analysis for the country shows that temperatures are already increasing and rainfall trends are dominated by year-to-year variability. Livelihoods and agricultural production systems are already being affected by the changing and more variable climate. Climate projections for the 2050s show strong agreement for an increase in temperature, but no strong trend for changes in rainfall. All scenarios of projected climate change will result in increased heat stress, reductions in water availability, and more frequent and intense extreme weather events, which could exacerbate food insecurity in the absence of adaptation.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas; security / segurança

Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Scenarios for Violence in the Resource-rich Cabo Delgado Province - Devermont, Judd; Columbo, Emilia (Center for Strategic and International Studies (CSIS), 2019)
The government of Mozambique has a rapidly shrinking window within which to implement a more comprehensive and effective strategy to weaken the Ahlu Sunna wa Jama (ASWJ) insurgents in Cabo Delgado and prevent the group from becoming an entrenched, long-term security problem. This report projects that the security situation in Cabo Delgado will most likely deteriorate during the next 18 months if the ASWJ insurgency continues to recruit new fighters and maintains a high frequency of attacks, as they have done since October 2017. Another key destabilizing factor is a government response that prioritizes military action over community development programs as its primary line of effort against the group. The government’s heavy-handed counterinsurgency approach risks further alienating the local population, driving them to lend active and passive aid to the militants. While the complete pacification of the group is unlikely during the next 18 months, a concerted whole-of-government approach would help undercut the group’s momentum. This includes outreach to the local community, programs, and policies designed to address specific grievances, and the use of targeted military operations. Maputo’s partners in the international community and private sector also have an important role to play. They can leverage their political influence and financial resources to press the Mozambican government to shift its current approach toward one that addresses the underlying grievances driving the insurgency. In doing so, Maputo and its partners have a better opportunity to not only undercut the present violence but potentially prevent future armed groups from emerging.
Keywords: G - Mozambique / Moçambique; GP - Cabo Delgado; L - english / inglês; security / segurança; ⛔ No DOI found